The Effectiveness of Mindfulness Training- Cognitive Bias Modification in Reducing Anxiety Symptoms - Khadir Zareh, Maryam; Sohrabi, Ahmad (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2020)
Background and Purpose: Early conceptualizations of anxiety indicate that maladaptive cognitions cause and maintain anxiety disorders so that anxious people show bias in processing information, prefer to pay attention to threatening stimuli, and interpret emotional ambiguity in a threatening direction. Therefore, the present study aimed to examine the effectiveness of mindfulness training-attention bias modification in reducing anxiety symptoms. Methods: The current research method was quasi-experimental with a pretest-posttest design, and a control group. The statistical population consisted of experimental and control groups of students at the University of Kurdistan; hence, 31 students were selected by convenience sampling through recall and randomly assigned to experimental and control groups. Before and after the intervention, the participants responded to the Beck Anxiety Inventory (BAI) and the Spielberger state-trait anxiety inventory, as well as the dot-probe test. Results: The analysis of results using the repeated measures univariate analysis of variance (ANOVA) indicated a significant effect of the intervention and showed that the combined treatment of cognitive bias modification with mindfulness training reduced anxiety scores (beck, state, trait), and also reduced attention bias towards the threat. Conclusion: The results indicated that mindfulness- attention bias modification in the present study had the necessary efficiency to reduce social anxiety; hence, the therapy was effective.